Unmasking the mitochondrial mystery: febrile illness exposing a rare cause of refractory epilepsy with unique imaging features: a case report - Nikhita Suzanne Roshan; K. Vimala Christina Colaco; Fathima Raeesa; Safwan Ahmed (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background Mitochondrial DNA polymerase, which is encoded by the POLG (polymerase gamma) gene, is responsible for the replication of the mitochondrial genome. Around 300 pathogenic variants have been identified in this gene and the clinical impact of POLG mutations is highly variable in both severity and phenotype. Our case had a clinical presentation distinct from the known mitochondrial syndromes associated with POLG gene, in the form of refractory focal seizures against a background of progressive ataxia, late symptom onset and rapid progression. In addition, our patient had signal changes in the pons with a unique radiological feature not previously described in this disease. Case presentation We describe a 46-year-old lady with adult onset refractory focal seizures against a background of progressive cognitive impairment and ataxia preceded by a febrile illness. MRI brain showed T2/FLAIR hyperintensities involving right frontal and parietal cortex, bilateral thalamus, pons and cerebellum. Clinical exome and mitochondrial genome sequencing identified homozygous missense variation in exon 13 of the POLG gene. Among these above radiological features, a novel radiological finding in a case of POLG mutation was the transverse pontine signal change, which has not been described till date to our knowledge. She was being treated and given increasing doses and combinations of anti-seizure medications, but succumbed to the illness after two months. Conclusions This case highlights a unique radiological finding in the form of transverse T2/FLAIR signal change in pons, in a case of genetically proven case of POLG mutation along with other common radiological features. The triad of clinical features, which were characterised by progressive ataxia, cognitive impairment and refractory focal seizures occurring in combination, were unusual in a middle aged lady with POLG mutation.